Improved estimation of cucumber leaf photosynthetic acclimation to day-to-day changing photosynthetic photon flux density - Liyao Yu; Kazuhiro Fujiwara; Ryo Matsuda (BMC Plant Biology)
Abstract Background Plant leaves adjust their properties under changing photosynthetic photon flux density (PPFD) through acclimation. Accurate estimation of leaf photosynthetic properties (e.g., maximum photosynthetic rate, A max) using experienced PPFD helps to estimate canopy photosynthesis. So far, A max and its underlying properties could reportedly be estimated using a simple average PPFD (Q a) in recent days or weeks. We have recently proposed a time-weighted average PPFD (Q w), which improved the estimation of leaf mass per area but not that of photosynthetic properties of cucumber leaves. Results on cucumber leaves exposed to a one-day increase or decrease in PPFD at different timings suggested that responses of photosynthetic properties to an increase or decrease in PPFD were asymmetrical, with different extents and lengths of time lag. Results To incorporate these asymmetrical responses, we calculated a Q’a, in which Q a was calibrated by time-weighting the change of PPFD from the previous day, ΔQ(t). A test using measurement data under random day-to-day PPFD showed that this method using Q’a achieved more accurate estimations (determination coefficient, R 2 = 0.77) of photosynthetic properties than those using Q a or Q w (R 2 = 0.68). Moreover, the optimal weight trends of ΔQ(t) were asymmetrical, consistent with those suggested by our previous independent measurement data. This asymmetry was also confirmed by experiments, where photosynthetic properties acclimated faster to a decrease in PPFD than to an increase in PPFD. Conclusion Our results indicate that these asymmetrical responses to changes in PPFD should be incorporated to improve the estimation of photosynthetic properties.